Training on Making Crackers From Manalagi Mango Pulp as Healthy Snacks for Students of SMA Muhammadiyah Kedawung - Gusman, Tania Avianda; Ramadhani, Putri; Sodikin, Sodikin; Nurudin, Arif (Edumedia Solution, 2025)
This community service activity aims to process Manalagi mango flesh into healthy and economically valuable snacks, which are one of the local wisdom fruits typical of Cirebon. This community service activity begins with observation, socialization, training, and evaluation so that SMA Muhammadiyah Kedawung students can understand how to process mango flesh, which is abundant and valuable in the school garden. The results of this community service are crackers that have the distinctive taste and aroma of Manalagi mango and have nutrition and economic value. This activity can also invite SMA Muhammadiyah Kedawung students to be more creative and innovative in processing local wisdom fruits, which are abundant in the school garden, into healthy snacks.